The education and Life Skills - Bouderdaben, Amina (Journal of Human Sciences, 2020)
This study highlights the subject of life skills, that are known as soft skills. There is a growing body of evidence that success at school, at work and in life, must be supported and improved by a wide range of skills and values that can be developed and promoted through education systems: education based on life skills is designed to bridge the gap that has always been criticized by specialists between school and life. A teaching that traditional educational approaches could not fill due to the limits of the teaching given in their traditional classrooms, and focused on the transmission of knowledge without skills. Competency-based education comes as an inevitable alternative to 21st century education and learning as part of a holistic, transformative vision of education to increase and enhance full human potential